Synthesis of szentiamide, a depsipeptide from entomopathogenic Xenorhabdus szentirmaii with activity against Plasmodium falciparum - Nollmann, Friederike I.; Dowling, Andrea; Kaiser, Marcel; Deckmann, Klaus; Grösch, Sabine; ffrench-Constant, Richard; Bode, Helge B. (Beilstein Journal of Organic Chemistry, 2012)
The synthesis of the recently characterized depsipeptide szentiamide (1), which is produced by the entomopathogenic bacterium Xenorhabdus szentirmaii, is described. Whereas no biological activity was previously identified for 1, the material derived from the efficient synthesis enabled additional bioactivity tests leading to the identification of a notable activity against insect cells and Plasmodium falciparum, the causative agent of malaria.
Keywords: cyclic depsipeptide; esterification; natural product; szentiamide; Xenorhabdus